Are poetic similes cognitively constrained? A case of Malay poetic similes - Mohd Kasim, Zalina (Universiti Putra Malaysia Press, 2013)
This study examines the application of Cognitive Constraint Theory (CCT) to Malay poetic similes. Based on this theory, poetic structures like simile, zeugma and synaesthesia are in fact, governed by certain cognitive principles. These principles or "cognitive constraints", as they are better known within this approach, ensure the interpretability of the poetic structures on the part of the reader. In this study, a corpus of 587 Malay similes from twentieth century poems were analysed using the methodological framework introduced by Yeshayahu Shen, the proponent of CCT. The study showed that while Cognitive Constraint Theory works at a high level of generality, a more detailed analysis considers the effects of culture, history and specific linguistic choices.